Significance of Human Rights Education - Gupta, Dinesh Kumar (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2020)
Human Rights are those minimum rights which every individual must have against state or other public authority by virtue of his/her being a member of human family irrespective of any other consideration. Human Rights could be generally defined as those which are inherent in our nature and without which we cannot live as human beings. Human rights are rights inherent to all human beings, whatever our nationality, place of residence, sex, national or ethnic origin, color, religion, language, or any other status. We are all equally entitled to our human rights without discrimination. These rights are all interrelated, interdependent and indivisible. All human rights are indivisible, whether they are civil and political rights, such as the right to life, equality before the law and freedom of expression; economic, social and cultural rights, such as the rights to work, social security and education, or collective rights, such as the rights to development and selfdetermination, are indivisible, interrelated and interdependent. The improvement of one right facilitates advancement of the others. Likewise, the deprivation of one right adversely affects the others. Human rights education, fast becoming another global educational phenomenon, appears to be developing along equally varied, but more substantively focused and prescriptive lines, human rights bring not only the element of concrete experience and observable social conditions but also a much needed normative and prescriptive dimension. It is commonly recognized that human rights are the firm foundations of human existence and coexistence; that human rights are universal, indivisible and interdependent; and that human rights lie at the heart of all that the United Nations was created for and aspires to achieve in peace and development.